2010
DOI: 10.1021/jf1029493
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Polyphenolic Composition and Antioxidant Activity of New Sherry Vinegar-Derived Products by Maceration with Fruits

Abstract: Several experiments of maceration of a sherry wine vinegar with different fruits (orange, lemon, strawberry, grapefruit, and lime) have been carried out. After optimization (only peel, no heating and seven days as maximum time of maceration), parameters such as polyphenolic content, superoxide anion scavenging ability (related to antioxidant activity) and ascorbic acid content were determined in sherry wine vinegars macerated with two amounts of peel and for two maceration times (3 and 7 days). The analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…A number of studies have described the antioxidant properties of vinegars [26,31,32,33]. A more detailed analysis was presented by Ubeda et al [34], who focused on the effect of different processing techniques on antioxidant activity and total phenols during a laboratory production of persimmon vinegars.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have described the antioxidant properties of vinegars [26,31,32,33]. A more detailed analysis was presented by Ubeda et al [34], who focused on the effect of different processing techniques on antioxidant activity and total phenols during a laboratory production of persimmon vinegars.…”
Section: Discussionmentioning
confidence: 99%
“…Many phenolic‐rich compounds are present in vinegars, wines, fruits and herbs to a large extent . On the one hand, certain hydroxycinnamic acids, such as caffeic acid and p ‐coumaric acid, and their ester derivatives are the main polyphenolic compounds present in wines and vinegars, according to several authors . Moreover, gallic acid, protocatechuic acid and furfural compounds have also been identified in the aformentioned raw materials .…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of DSA and DFA are lower in common rice vinegar (polished rice vinegar), but higher in Kurosu, so Kurosu is more advantageous than polished rice vinegar as an antioxidative food item (Shimoji et al 2002). In addition, the presence of phenolic compounds can significantly affect the aromatic quality (Qingping 2006), and several papers suggested that phenolic compounds also play a key role in the antioxidant activity of vinegar (Cejudo Bastante et al 2010;Xu et al 2007). …”
Section: Physicochemical Properties and Compounds In Different Types mentioning
confidence: 98%
“…Furthermore, the main difference between European vinegar and Chinese vinegar is the raw materials used. European vinegar is usually produced from cider, wine, malted barley, fruit honey, pure alcohol, or juices, whereas Chinese vinegar is always produced from wheat bran, rice, and sticky rice as raw materials (Castro Mejıás et al 2002;Lipp et al 1998;Zhang et al 2006). In vinegar fermentation, the selection, preparation, and fermentation of raw materials are crucial because one of the most possible causes of strain diversity in AF and AAF can be the effect of raw material composition ).…”
Section: The Relationship Between Microbial Diversity and Raw Materialsmentioning
confidence: 99%
See 1 more Smart Citation